Loss of peptidase D binding restores the tumor suppressor functions of oncogenic p53 mutants - Lu Yang; Yun Li; Arup Bhattacharya; Yuesheng Zhang (Communications Biology, 2021)
Yang et al. report a mechanism of restoration of tumor suppressor activity of mutant p53 by disrupting its binding to peptidase D, leading to posttranslational modification, refolding and reactivation of the protein and its inhibition of cancer cell growth in vivo and in vitro. This finding presents a new possibility of “reactivating” mutant p53 and reveals a new therapeutic approach for a large number of human tumors.